Hochschild Cohomology and Deformations of Clifford-Weyl Algebras - Musson, I.M.; Pinczon, G.; Ushirobira, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We give a complete study of the Clifford-Weyl algebra C(n,2k) from Bose-Fermi statistics, including Hochschild cohomology (with coefficients in itself). We show that C(n,2k) is rigid when n is even or when k ≠ 1. We find all non-trivial deformations of C(2n+1,2) and study their representations.